2008
DOI: 10.1071/ah080292
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to continuing medical education in Australian prevocational doctors

Abstract: To determine perceived barriers to continuing education for Australian hospital-based prevocational doctors, a cross sectional cohort survey was distributed to medical administrators for secondary redistribution to 2607 prevocational doctors from Although these individual groups have over-arching representative governing bodies, they have traditionally existed with minimal consultation and collaboration, leading to a fragmented approach to education. 4 Inadequate funding for education, documented by the Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
2
13
0
2
Order By: Relevance
“…This made attendance difficult, despite these sessions occurring during “protected time” (unpublished data). This is consistent with previous research findings which have shown that junior doctors find it difficult to choose between patient care, work demands and their own professional development (PD) 1 …”
Section: Boxsupporting
confidence: 93%
“…This made attendance difficult, despite these sessions occurring during “protected time” (unpublished data). This is consistent with previous research findings which have shown that junior doctors find it difficult to choose between patient care, work demands and their own professional development (PD) 1 …”
Section: Boxsupporting
confidence: 93%
“…In addition, none of these studies have addressed the barrier to practicing CME as the main objective, apart from one study done at hospital level [17]. Furthermore, none of them undertook an in-depth analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study conducted in Australia involving 437 prevocational doctors, 85% identified lack of time as the main barrier to practicing CME followed by clinical commitment (65%), workload issues (27%), teaching program inadequacies (26%), lack of protected time for education (17%), resistance from registrars (13%), resistance from consultants (10%), motivational issues (11%), and geographic remoteness [17]. Another Australian study shows that the local general practitioners' main barriers to CME were lack of time and loss of income [18].…”
Section: Introductionmentioning
confidence: 99%
“…Junto con lo anterior, la percepción de ser "buen docente" y la escasa autocrítica de las propias habilidades docentes, la falta de reconocimiento académico y de incentivos económicos asociados a la docencia, emergen como barreras confi rmando los hallazgos en otros estudios [17][18][19][20][21] . Sin embargo, otros obstáculos para la capacitación en docencia, tales como la lejanía física y la falta de sentido de pertenencia a la institución no fueron mencionados por los entrevistados [28][29] .…”
Section: Discussionunclassified
“…Si bien existen algunas investigaciones sobre el problema de la falta de asistencia de los profesores de medicina a cursos de capacitación en docencia en otros países, no había estudios en la realidad local, por lo que pareció relevante conocer en profundidad lo que estaba ocurriendo en la EMUC [16][17][18][19][20] . El objetivo de este estudio fue explorar los factores que difi cultan que los académicos de la EMUC asistan a los cursos del DEM.…”
unclassified